(untitled) (Annals of Medical Research, 2021)
Aim: Our purpose was to determine the presence of inflammation in Fibromyalgia Syndrome (FMS), whether the parameters of neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) and mean platelet volume (MPV) can be used as inflammation markers.Materials and Methods: FMS patients who applied to Hatay State Hospital Physical Medicine and Rehabilitation Clinic in the last two years were analyzed retrospectively from the patient records. 92 participants were enrolled in the study, 43 of them were FMS patients, and 49 were healthy control group. Hemogram, glucose levels, hepatic panel and renal function tests, thyroid and parathyroid function testing, vitamin B12 and 25-hydroxyvitamin D, serum iron panel, folate, lipid panel, erythrocyte sedimentation rate (ESR), C-reactive protein, RF, Bucella agglutination test results were evaluated. Thus, patients with diseases that could affect NLR, PLR, and MPV were not enrolled in the study.Results: No significant difference between the groups in terms of gender distribution was found (p = 0.999). No significant difference between the groups in terms of age was found (p=0.327). When the groups were compared in terms of MPV, the values were found to be lower in the FMS group. Statistically significant difference was not found in both groups in terms of NLR, PLR, White blood count (WBC) and Platelet (PLT) levels (p=0.106; p=0.710; p=0.271; p=0.141, respectively).Conclusion: A significant difference was not found in both groups in terms of NLR and PLR, which were thought to be inflammation markers. The statistically significant higher values of mean ESR values in the FMS group indicate that inflammation may be present in the pathogenesis of FMS, but NLR and PLR cannot be used as indicators of inflammation, so correlating these rates with the severity of symptoms would be meaningless.